I am reading section 12 (Flipping Moduli) of the paper "The polynomial $X^2+Y^4$ captures its primes".

At page 997, just below equation (12.7) we start estimating the following sum $$ V(f,g)=\sum_d f(d)\sum_{\substack{r_1s_2\equiv r_2s_1 (d)\\}} \alpha_{r_1,s_1}\bar{\alpha}_{r_2,s_2}\left(\frac{d}{r_1r_2}\right)g\left(\left|\frac{s_1}{r_1}-\frac{s_2}{r_2}\right|\right) $$ where $R\leq r\leq 2R$, $S\leq s\leq 2S$ and $f$ is supported on $\frac{1}{2}D\leq d\leq 3D$. They start by reducing the variables $r_1, r_2$ by the common divisor $c=(r_1,r_2)$ and removing the resulting condition $(c,d)=1$ (we know that both $r_1$ and $r_2$ are coprime to $d$, hence so is their gcd) by Mobius inversion, i.e. $$ 1_{\text{gcd}(c,d)=1}=\sum_{m|\text{gcd}(c,d)}\mu(m) $$ Using these tools we obtain equation (12.8) $$ V(f,g)=\sum_c\sum_{m\mid c}\mu(m)V_{c,m})(f,g) $$ where $V_{c,m}(f,g)$ is defined as $$ V_{c,m}(f,g)=\sum_d f(dm)\sum_{\substack{r_1s_2\equiv r_2s_1 (dm)\\ (r_1,r_2)=1}}\alpha_{cr_1,s_1}\bar{\alpha}_{cr_2,s_2}\left(\frac{d}{r_1r_2}\right)g\left(\left|\frac{s_1}{r_1}-\frac{s_2}{r_2}\right|\right) $$ They then proceed to obtain a bound for $V_{c,m}(f,g)$. After two pages they are able to prove the following bound (the inequality after equation (12.16)) \begin{equation} V_{c,m}(f,g)\ll\left\{(cm)^{-1/2}(DHRS)^{1/2}(2\log 2RS)^3 +\left[c^{-3/2}mD^{-1}(RS)^{3/2}+RS^{3/4}+SR^{3/4}\right](RS)^\epsilon\right\}\sum_{r,s}|\alpha_{cr,s}|^2 \end{equation} They then say that summing over this bound over $m$ and $c$ as in equation (12.8) yields $$ V(f,g)\leq \mathcal{H}(D,H,R,S)\sum_r\sum_s\tau(r)|\alpha_{r,s}|^2 $$ where $\mathcal{H}(D,H,R,S)$ satisfies the bound \begin{multline} \mathcal{H}(D,H,R,S)\ll (DHRS)^{1/2}(\log 2RS)^4\\ +\left[D^{-1}(RS)^{3/2}+RS^{3/4}+SR^{3/4}\right](RS)^\epsilon \end{multline} I am not able to understand how summing over $m$ and $c$ yields this bound. In particular what is the range over which $c$ varies? I think it would suffices to prove the following bounds $$ \sum_c\sum_{m\mid c}\mu(m)(cm)^{-1/2}\ll \log 2R $$ and $$ \sum_c\sum_{m\mid c}\mu(m)(c)^{-3/2}m\ll \log 2R $$ I am able to show, using the multiplicativity of $\mu$ that $$ \sum_{m\mid c}\mu(m)m^{-1/2}\leq 1\qquad\text{ and }\qquad\sum_{m\mid c}\mu(m)m\leq c $$ Using this both equations reduce to showing that $$ \sum_c c^{-1/2}\ll \log 2R $$ but I don't know if what I have done so far is correct and I should I proceed now. Thank you!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.